One‐year COVID‐19 outcomes on the oncology care patient pathway: Results of a French descriptive, cross‐sectional comprehensive study (ONCOCARE‐COV). (20th May 2022) - Laurent, Léonard; Brugel, Mathias; Carlier, Claire; Clere, Florentin; Bertrand, Aurélie; Botsen, Damien; Boulagnon‐Rombi, Camille; Dalstein, Véronique; Debreuve‐Theresette, Adeline; Deguelte, Sophie; Garbar, Christian; Mahmoudi, Rachid; et al.
Abstract: Background: The COVID‐19 pandemic led to a widely documented disruption in cancer care pathway. Since a resurgence of the pandemic was expected after the first lockdown in France, the global impact on the cancer care pathway over the year 2020 was investigated. Aims: This study aimed to describe the changes in the oncology care pathway for cancer screening, diagnosis, assessment, diagnosis annoucement procedure and treatment over a one‐year period. Materials & Methods: The ONCOCARE‐COV study was a comprehensive, retrospective, descriptive, and cross‐sectional study comparing the years 2019 and 2020. All key indicators along the cancer care pathway assessing the oncological activity over four periods were described. This study was set in a high‐volume, public, single tertiary care center divided in two complementary sites (Reims University Hospital and Godinot Cancer Institute, Reims, France) which was located in a high COVID‐19 incidence area during both peaks of the outbreak. Results: A total of 26, 566 patient's files were active during the year 2020. Breast screening (−19.5%), announcement dedicated consultations (−9.2%), Intravenous and Hyperthermic Intraoperative Intraperitoneal Chemotherapy (HIPECs) (−25%), and oncogeriatric evaluations (−14.8%) were heavily disrupted in regard to 2020 activity. We identified a clear second outbreak wave impact on medical announcement procedures (October, −14.4%), radiotherapy sessions (October, −16%), number of new health record discussed in multidisciplinary tumor board meeting (November, −14.6%) and HIPECs (November, −100%). Moreover, 2020 cancer care activity stagnated compared to 2019. Discussion: The oncological care pathway was heavily disrupted during the first and second peaks of the COVID‐19 outbreak. Between lockdowns, we observed a remarkable but non‐compensatory recovery as well as a lesser impact from the pandemic resurgence. However, in absence of an increase in activity, a backlog persisted. Conclusion: Public health efforts are needed to deal with the consequences of the COVID‐19 pandemic on the oncology care pathway. Abstract : Key steps in the oncology care pathway activity were retrospectively analyzed and compared in this comprehensive and cross‐sectional study, between the different time settings in the COVID‐19 pandemic. Oncology care were heavily disrupted during the first and second COVID‐19 outbreak waves with decrease in screening and diagnosis activity as well as an uncommon stagnation in treatment activity. A backlog has inevitably persisted after the disruptions caused by the first and second outbreak waves even though a between‐lockdown recovery occurred in between. Public health efforts are needed to deal with the consequences